Portable UV-spectrophotometer to determine the concentration of potassium - Kabir, Ifran; Hossain, Md. Taushik; Al-Amin, Md.; Shupta, Jahanara Akter (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.